Analisis Implementasi Kebijakan Dalam Penggunaan Dana APBN Dan DAK Di Kabupaten Jayawijaya Tahun Anggaran 2012-2014 - Indahyani, Rachmaeny (Jurnal Kajian Ekonomi dan Studi Pembangunan, 2015)
This study generally aims to analisys implementation and recommendation policy for alocation budget APBN and DAK TA 2012-2014 in Jayawijaya City. More specific, the objectives are: (a) determine and analyze planning programing alocation budget APBN and DAK TA 2012-2014 in Jayawijaya City, (b) identify and analyze Implementation alocation budget APBN and DAK TA 2012-2014 in Jayawijaya and c) Recommendation budgeting policy for future planning budgeting. Keywords: Planing Programming, Implementation Programming, Monitoring and Evaluation, Recommendation Budgeting Policy